2017
DOI: 10.1080/21691401.2017.1345926
|View full text |Cite
|
Sign up to set email alerts
|

A key role of microRNA-26a in the scar formation after glaucoma filtration surgery

Abstract: Glaucoma is one of the leading causes of blind worldwide. Post-operative scar formation of filtering tract was one of the main reasons for failure of glaucoma filtration surgery. In this study, we conducted several experiments to detect the expression of miR-26a in the scar tissue in filtering tract and then detect its potential biological effects as well as its target gene. In our present study, it was found that miR-26a was significantly down-regulated in filtering tract scar. Advanced study on the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Abnormal expression of miRNAs may contribute to the management of skin fibrotic diseases ( 25 ). A recent study investigated the role of miR-26a in scar formation following glaucoma filtration surgery and the findings suggested that miR-26a served an essential role in filtering tract scar formation ( 26 ); however, these results were limited to the role of miR-26a in postoperative scar formation. The present study was conducted to investigate the role of miR-26a in HS.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of miRNAs may contribute to the management of skin fibrotic diseases ( 25 ). A recent study investigated the role of miR-26a in scar formation following glaucoma filtration surgery and the findings suggested that miR-26a served an essential role in filtering tract scar formation ( 26 ); however, these results were limited to the role of miR-26a in postoperative scar formation. The present study was conducted to investigate the role of miR-26a in HS.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence implicates mircoRNAs (miRNAs) as important regulatory factors in tumorigenesis and hypertrophic scars, and they are found to be dysregulated in the majority of analyzed cancers and pathological scars [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that expression of microRNA-26a was significantly down regulated in the HSs after glaucoma filtration surgery. 17 Overexpression of microRNA-26a has been proved to reduce the expression of collagen fibers in keloid and to restrain the occurrence of skin fibrosis. 18 In this study, the expression of microRNA-26a in HSs was significantly up- regulated after the treatment via triamcinolone acetonide, suggesting that microRNA-26a might be involved in the development of HS and its pathological process.…”
Section: Discussionmentioning
confidence: 99%